Optimalisasi Keuntungan Produksi Makanan Dengan Menggunakan Pemrograman Linear Melalui Metode Simpleks: Studi Kasus : Dapur Orens - Bunga Karnelia; Rizkia Amelia Hanum; Risya Alica Dwiyana; Sifani Jannah (Journal of Creative Student Research, 2024)
This research aims to examine the role and contribution of Micro, Small and Medium Enterprises (MSMEs) in the Indonesian economy, as well as to apply linear programming via the simplex method in optimizing food production profits in the Dapur Orens case study. This research uses quantitative methods with interview techniques as data collection. The data obtained was then analyzed using interactive analysis models and triangulation methods. The research results show that MSMEs have an important role in driving GDP growth and absorbing labor, but still have challenges in accessing global supply chains. Apart from that, the research results also show that by using the simplex method, Dapur Orens can maximize food production profits by determining the optimal quantity of two mainstay menus, namely tondaru chicken and rica-rica chicken, taking into account the limited raw materials available. It is hoped that this research will provide benefits for MSME actors, developers and researchers, as well as for Dapur Orens in increasing the efficiency and effectiveness of food production.